Performance analysis in field hockey goalkeeping during penalty corners: a case study - Ruscello, B.; Mitrotta, F.; Dring, M. B.; Partipilo, F.; D'Ottavio, S. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The purpose of this study is to investigate the kinematics of field hockey goalkeeping during penalty corners, in order to provide the first model of performance from a physical standpoint during this particular and important phase of goalkeeping that goes from the injection of the ball (the push-in) up to the shot on goal during a penalty corner. In particular, the focus was on the preparation phase before the actual saves.